1993
DOI: 10.1017/s0952523800003291
|View full text |Cite
|
Sign up to set email alerts
|

Photopigments of dogs and foxes and their implications for canid vision

Abstract: Electroretinogram (ERG) flicker photometry was used to examine the photopigment complements of representatives of four genera of Canid: domestic dog (Canis familiaris), Island gray fox (Urocyon littoralis), red fox (Vulpes vulpes), and Arctic fox (Alopex lagopus). These four genera share a common cone pigment complement; each has one cone pigment with peak sensitivity of about 555 nm and a second cone pigment with peak at 430–435 nm. These pigment measurements accord well with the conclusions of an earlier inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 23 publications
(22 reference statements)
1
50
0
5
Order By: Relevance
“…A similar phenomenon has been shown to underlie the loss of S cones among cetaceans (Levenson and Dizon 2003). The absence of S cones in pinnipeds is remarkable as the vast majority of terrestrial mammals studied have been found to possess both S and M/L cone visual pigments (Jacobs 1993;Jacobs et al 1993;Yokoyama and Yokoyama 1996) with a loss of S cones limited to isolated occurrences at the most distal branches of the primate, carnivore, and rodent lineages (e.g., Jacobs et al 1996b;Peichl and Moutairou 1998). The convergent widespread loss of S cones in these two divergent marine mammal groups suggests that the absence of this cone type may be linked to adaptation for aquatic vision; for example, to produce a reduction in sensitivity to the short wavelengths which are highly scattered in aquatic environments and hence potentially not conducive to good spatial vision (see Peichl et al 2001, Cowing et al 2002.…”
Section: Discussionmentioning
confidence: 58%
“…A similar phenomenon has been shown to underlie the loss of S cones among cetaceans (Levenson and Dizon 2003). The absence of S cones in pinnipeds is remarkable as the vast majority of terrestrial mammals studied have been found to possess both S and M/L cone visual pigments (Jacobs 1993;Jacobs et al 1993;Yokoyama and Yokoyama 1996) with a loss of S cones limited to isolated occurrences at the most distal branches of the primate, carnivore, and rodent lineages (e.g., Jacobs et al 1996b;Peichl and Moutairou 1998). The convergent widespread loss of S cones in these two divergent marine mammal groups suggests that the absence of this cone type may be linked to adaptation for aquatic vision; for example, to produce a reduction in sensitivity to the short wavelengths which are highly scattered in aquatic environments and hence potentially not conducive to good spatial vision (see Peichl et al 2001, Cowing et al 2002.…”
Section: Discussionmentioning
confidence: 58%
“…11 These are termed long-and medium-wavelength-absorbing cones (L/M cones) and short-wavelength-absorbing cones (S cones), and have maximal sensitivities of 555 nm and 429-435 nm, respectively. 12,13 Canine diseases with primary cone photoreceptor involvement include achromatopsia and X-linked progressive retinal atrophy (XLPRA).…”
Section: Introductionmentioning
confidence: 99%
“…We did not convert the images to grayscale as in another study of egg coloration and nest survival (Lee et al 2010). Nest depredation of Mountain Plovers by predators such as canids, which view the world dichromatically (Jacobs et al 1993), have been observed primarily at night and the animals appeared to find the nest by scent rather than sight ( personal observations).…”
Section: Discussionmentioning
confidence: 99%